Fiscal calculus in a New Keynesian model with matching frictions - Alessia Campolmi; Ester Faia; Roland C. Winkler (Kiel Institute for the World Economy (IfW), 2010)
The endorsement of expansionary fiscal packages has often been based on the idea that large multipliers can contrast rising unemployment. Is that really the case? We explore those issues in a New Keynesian model in which unemployment arises because of matching frictions. We compare fiscal packages with different targets (pure demand stimuli versus subsidy to cost of hiring) and of government funding (lump sum taxation versus distortionary taxation). We find that in presence of demand stimuli fiscal multipliers are zero and even turn negative when financed with distortionary taxation. On the other side, in a model with a non-Walrasian labor market, policies aimed at reducing labor wedges, such as cost of hiring, are particularly effective in boosting employment and output.
Keywords: E62; E63; E24; 330; Fiscal calculus; taxation; matching frictions; Antizyklische Finanzpolitik; Multiplikator; Steuersystem; Wirkungsanalyse; Beschäftigungseffekt; Ungleichgewichtstheorie; Arbeitsmarkt; Matching; Theorie